Nonmelanoma skin cancers: An Indian perspective - Geeti Khullar; Uma Nahar Saikia; Dipankar De; Bishan Das Radotra (Wolters Kluwer Medknow Publications, 2014)
Nonmelanoma skin cancers (NMSCs), which mainly include basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), are infrequent in the Indian subcontinent, compared with white skinned individuals. Although BCC in most cases arises de novo on sun-exposed sites, it may rarely develop in photoprotected areas and in the setting of certain risk factors. In contrast to BCC, SCC in dark skin has a tendency to develop in nonhealing ulcers, chronic scars, and inflammatory and infectious dermatoses. Histopathology is the gold standard in confirming the diagnosis and determining the prognosis. As the existing literature on NMSCs in India is limited mostly to case reports and few reviews only, this article is an attempt to create an awareness regarding the premalignant potential of an expanding list of cutaneous lesions, which would help in timely diagnosis and prompt treatment of NMSCs.